EMERGENCE CURRICULUM TO MITIGATE LITERACY LOSS AT THE ELEMENTARY SCHOOL LEVEL - Siti Hapsoh Riani; Fentiny Nugroho (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The Covid-19 pandemic has exacerbated the literacy skills of elementary school students in Indonesia. The technical and non-technical constraints during distance learning result in literacy loss, which should be minimized as early as possible. Adjustment of learning systems and policies helps prevent the potential for literacy loss, one of which is implementing emergency curriculum policies issued by the Ministry of Education and Culture. The emergency curriculum policy was created to reduce learning obstacles students, teachers, and parents face due to the suboptimal implementation of Distance Learning. This study utilized a literature review method by providing an emergency curriculum policy to mitigate literacy loss in elementary school students. This policy contains several modules for children, teachers, and parents whose material focuses on basic literacy and numeracy needs, focusing on essential competencies and prerequisite competencies to support continuous learning. Thus, the emergency curriculum policy can be one of the ways to overcome disparities in human development and one of the ways to overcome current social development problems.